If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + -1) + -7x = 16 Reorder the terms: 3(-1 + 4x) + -7x = 16 (-1 * 3 + 4x * 3) + -7x = 16 (-3 + 12x) + -7x = 16 Combine like terms: 12x + -7x = 5x -3 + 5x = 16 Solving -3 + 5x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 5x = 16 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = 16 + 3 5x = 16 + 3 Combine like terms: 16 + 3 = 19 5x = 19 Divide each side by '5'. x = 3.8 Simplifying x = 3.8
| 5x+26+14x=82 | | 2x^2+8=32 | | 3^(-4)/3 | | 32-3x=6x+21 | | x/7 | | 5x-8=2x+29 | | 3+5x+5x=83 | | 7x+2=4-(4x-7) | | 222-4x=179-44x | | 4x+7=x-5 | | -39-6x=-8x+11 | | 10/21=2a/a+b | | 10x-114=5x-14 | | 3x+7=-48-8x | | 160-4x=6x+10 | | 1ox-114=5x-14 | | 18p+33= | | 3x-9+7x=101 | | 3a+2a=9 | | 2x-1=10x-50 | | 1=2r+9 | | -69=-3x-4(3x-3) | | 3(5x+2)=24 | | 11/3=v/8 | | 90-2x=25+18 | | 5x+8=-78-9x | | -6x+3(x+3)=36 | | 5x+27=4x-72 | | 6(3x-7)-3=6(x-3)+45 | | 69=-4x-5x+6 | | 5/6=x/24 | | 7n^2+7n-140= |